Study of Spectral Energy Distributions of low-luminosity radio galaxies at z 1–3: a high-z view of the host/AGN connection. Issue Volume 9:Issue S304(2013) (25th July 2014) - Baldi, Ranieri D.; Chiaberge, Marco; Capetti, Alessandro
Abstract: Low-luminosity radio galaxies, common in the local Universe, are associated with giant elliptical galaxies and typically with a FR I radio morphology. However, they are rare in flux-limited samples of distant radio-loud (RL) AGN due to a selection bias. Chiaberge et al . (2009) selected the first sizeable sample of FRI candidates at 1<z<3, in the COSMOS field. We study the Spectral Energy Distributions (SEDs) of this low radio power sample from the far-UV to the Mid-IR wavelengths. Our results show that the hosts of these high-z low-luminosity radio sources are old massive galaxies, similar to the local FR Is. However, for half of the sample the UV and MIR excesses indicate the possible significant contribution from star formation and/or nuclear activity, not seen in low-z FR Is. Our sources display a wide variety of properties: from possible quasars at the highest luminosities, to low-luminosity old galaxies.